Teacher Perceptions on the Possibility of Integrating History and Citizenship in the Lesotho Curriculum: A Case of Three Secondary Schools (Yesterday & Today Journal for History Education in South Africa and abroad, 2024)
One of the key contemporary needs in education is to promote nationalism and national cohesion. Challenges confronting most developing countries include political instability, violence, voter apathy, and youth disintegration. Many regard the teaching of citizenship as a possible panacea to remedy these problems. Scholars have applauded the role of citizenship education in inculcating crucial values such as active citizenship, tolerance, and social cohesion. The Lesotho curriculum uses social science subjects, especially history, to address these challenges. Pursuant to repeated calls for the integration of history with citizenship in Lesotho schools in order to enhance history’s thrust in achieving the task, this qualitative study adopted the case study design to purposively sample six history teachers, two from each of three secondary schools in the Maseru district. Semi-structured interviews and document analysis of the Education Sector Plan 2005-2015 and Education Sector Strategic Plan 2016-2026, Curriculum and Assessment Policy (CAP) 2009, Lesotho General Certificate of Secondary Education (LGCSE), and the Grade 8 Social Science Syllabus were relied upon for the collection of data. Our findings from this study show thatteachers believe that the integration of history and citizenship can instil values of active citizenship, patriotism, political stability, and economic development to mention but a few. We therefore concluded that there are possibilities of integrating history with citizenship instead of leaving them as subjects independent from each other. We recommend that the Ministry of Education and Training (MoET) should consider the integration of history and citizenship into the curriculum.
Keywords: integration; history; citizenship; curriculum; syllabus